Investigational fibroblast growth factor receptor 2 antagonists in early phase clinical trials to treat solid tumors. (3rd October 2019) - Wang, Dan; Yang, Li; Yu, Weina; Zhang, Yi
ABSTRACT: Introduction : Fibroblast growth factor receptor 2 (FGFR2) is a highly conserved transmembrane tyrosine kinase receptor. FGFR2 dysregulation occurs in numerous human solid tumors and overexpression is closely associated with tumor progression. FGFR2 has recently been reported as a therapeutic target for cancer. Several targeted therapies are being investigated to disrupt FGFR2 activity; these include multi-target tyrosine kinase inhibitors (TKIs), pan-FGFR targeted TKIs and FGFR2 monoclonal antibodies. Areas : This review examines FGFR2 regulation and function in cancer and its potential as a target for cancer treatment. Expert opinion : Highly specific FGFR2 blockers have not yet been developed and moreover, resistance to FGFR2-targeted therapies is a challenge. More sophisticated patient selection strategies would help improve FGFR2-targeted therapies and combination therapy is considered the most promising approach for cancer patients with FGFR2 alterations.